METHODOLOGICAL APPROACHES AND CHALLENGES IN ASSESSING THE VALUE OF INTELLECTUAL CAPITAL - E. D. Katulskij; N. A. Bespalova (Модернизация, инновация, развитие, 2017)
Presence at the enterprise znanievyh resources determines its capacity for sustainable and competitive development. The set of knowledge, skills and abilities (which has operational and management personnel), including transformed in intangible and other assets are considered to be the intellectual capital of the enterprise. Empirically, the presence of the intellectual capital of the enterprise can be identified by its success in the market and the ability to generate a high value added product. However, scientific and methodological point of view, approaches to assessing intellectual capital are currently not standardized and do not provide an objective valuation of the capital.This paper presents an overview of the methodological approaches to the valuation of the intellectual capital of companies and shows the problems of using these approaches in analytical procedures. Based on the materials conclusion about the necessity of further development of the intellectual capital evaluation methods enterprises it was made.The purpose / goal. The purpose of this article is to study the specifics of basic methodological approaches to the valuation of the intellectual capital of enterprises. Moreover, among the main tasks is to provide: an analysis of the most frequently used techniques in the Russian and international practice, assessment of intellectual capital.Methodology. The article is a content analysis of the theoretical and scientific-methodical positions, describing the key and the most frequently used Russian and international approaches to the evaluation of the intellectual capital of enterprises.Conclusions / relevance. The practical significance of this paper is to identify the main issues that arise in the evaluation of the intellectual capital of the enterprises, which determines the need for further scientific development and complement the currently used evaluation methods.